Market Structure And Behavior Analysis Swallow's Nest In Parigi Moutong District Central Sulawesi Province - Mila Rosita; Ria Indriani; Irwan Bempah (Cita konsultindo, 2025)
The swallow nest business in Parigi Moutong Regency has only started to develop in the last ten years. Although still relatively new, this area has become one of the export centers for swallow's nest commodities in Central Sulawesi. This study aims to analyze the structure, behavior, and performance of the swallow's nest market in Parigi Moutong Regency. The method used in this research is quantitative descriptive analysis using survey method. The data taken were primary data through direct interviews with the help of questionnaires and observations. Secondary data were obtained from literature. The results showed that the swallow nest market structure formed at the entrepreneur level is perfect competition. The market structure formed at the level of village traders and large traders is monopolistic. Swallow nest entrepreneurs sell their crops to village traders and large traders. Prices are determined by traders based on quality, quantity, and market conditions. However, entrepreneurs often have limited market information, resulting in a weak bargaining position. Village traders and large traders have better access to market price information, making them the price setters for entrepreneurs. The selling price of swallow's nest varies, with entrepreneurs selling to village traders at around IDR 6,000,000 per kilogram, while large traders offer prices between IDR 8,000,000 and IDR 9,000,000 per kilogram. The marketing function involves entrepreneurs, village traders, and wholesalers, each with a role in distribution and pricing. Marketing channel I, where entrepreneurs sell directly to large traders, provides higher prices than marketing channel II, which involves village traders as intermediaries.